The Catania Project 2D, 3D XRF microanalysis of Roman wall-paintings - Φωτίου, Σαββίνα (Πανεπιστήμιο Πελοποννήσου, 2019)
In this thesis three different modalities of XRF analytical techniques are performed on roman wall – painting fragments for pigment identification and exploration of paintlayer stratigraphy. Seven wall – painting fragments originated from two roman houses located in Sicily of Italy are analyzed. The techniques that were used for their analysis include 1D (depth), 2D (area) and 3D (volume) scan measurements performed by a micro confocal XRF system. The XRF results from the analysis of the roman wall – painting fragments have identified the application of the following pigments on a lime-based substrate: ochre, green earth, cinnabar, Cu based green (malachite /verdigris) and blue pigments (azurite). For certain pigments, specific elemental associations have been revealed between major and minor elements. Through the application of the 1D (depth) and 3D (volume) XRF methodologies the thickness of each paint layer as well as the paint stratigraphy of each sample is investigated. The in-depth (1D) elemental profiles of calcium coming from the preparation layer usually appears in the same depth with the paint layers pigments. It is not clear if that is the way that calcium behaves at different conditions and passing of the time or if Romans used a lime solution or just water to apply their pigments. Further systematic work is needed to better understand the ancient recipes and to evaluate possible degradation pathways.
Keywords: Τοιχογραφία και διακόσμηση, Ρωμαϊκή -- Ιταλία -- Τεχνική; Τοιχογραφία και διακόσμηση, Ρωμαϊκή -- Συντήρηση και αποκατάσταση; Υλικά βαφής -- Ανάλυση; Χρωστικές ουσίες -- Ανάλυση; Αναλυτική τεχνική XRF; Ρωμαϊκές τοιχογραφίες; Μικροανάλυση